2001
DOI: 10.1046/j.1439-0396.2001.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, body fat content and energy expenditure in intact and gonadectomized adult cats: a preliminary study

Abstract: The present study was conducted to assess the body composition, leptin, and energy expenditure changes following gonadectomy in cats. Twenty-one females (12 intact and nine spayed) and 21 males (11 intact and 10 castrated) were used. Body weight was recorded. Serum plasma leptin was measured by radioimmunoassay and body composition and energy expenditure were assessed after injection of doubly labelled water. These results confirmed the gain in body weight and body fat following neutering and demonstrated a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
52
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 19 publications
11
52
0
6
Order By: Relevance
“…Cats, similar to other species, have increased circulating leptin concentrations following weight gain. Increased blood leptin concentrations, without decreases in food intake suggests decreased leptin sensitivity (Appleton et al, 2000;Backus et al, 2000;Martin et al, 2001).…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 99%
“…Cats, similar to other species, have increased circulating leptin concentrations following weight gain. Increased blood leptin concentrations, without decreases in food intake suggests decreased leptin sensitivity (Appleton et al, 2000;Backus et al, 2000;Martin et al, 2001).…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 99%
“…Weight gain resulting in obesity occurs when EI exceeds EE over a period of time, and an increase in FI [4], [5] and decrease in EE [4], [6], [7] have both been suggested as mechanisms contributing to post-neutering weight gain. Several studies have reported that gonadectomy stimulates increased FI in cats [4], [5], [8].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents (4,18,21,81, 102) and domestic animals (26,35,58), ovariectomy consistently leads to a rapid increase in body weight and hyperphagia, and estradiol treatment reduces food intake and body weight (14,37,65,81,97). Ovariectomy rapidly increases body weight in nonhuman primates (89), and treatment of ovariectomized monkeys with estradiol has been shown to suppress food intake (24, 44).…”
mentioning
confidence: 99%